Experimental investigation on the effects of bifurcation angle on enhanced microscale heat transfer in macro geometry - Foo, Zi Hao (2018)
The effectiveness of microscale heat transfer in macro geometry has been demonstrated to produce comparable heat transfer performance to that of conventional microchannels. For this research, a microchannel was created by fitting an insert with nominal diameter 19.4 mm concentrically within a hollow cylinder with inner diameter 20.0 mm, thereby producing a microchannel with an annular gap of 300 µm. Surface profiles on the insert were optimised to recover pressure loss, aiming to address the increased pumping requirements that accompany the improvement in heat transfer capabilities. A bifurcation angle was incorporated into the offset fin geometry design. The increased heat removal capability at the same pumping power and the reduction of pumping power for the same heat removal duty for three different bifurcation angles, namely 70, 75 and 80 degrees, were investigated with respect to parallel channels. The experimental study was conducted at a constant heat flux of 500 W at Reynolds number ranging from 690 to 4600. The amount of fluid in the microchannel, heat transfer area, rate of heat supplied, average channel gap size, channel length and fin height were kept constant. Experimental results successfully validated the effectiveness of bifurcation angles in the recovery of pressure loss across the microchannel. As compared to parallel channels, the 80-degrees bifurcating fins displayed the highest enhancement of the heat transfer coefficient and greatest reduction of the pumping power, which are 27% enhanced and 52% reduced respectively, at a given heat removal duty.